Pembuatan dan Karakterisasi Dispersi Padat Nifedipin dengan Poloxamer 188 Menggunakan Metode Peleburan - Rina Wahyuni; Auzal Halim; Sri Oktavia; Rahmi Purwaningsih (STIFARM Padang, 2016)
Nifedipin is a poorly water soluble calcium channel blocking agent. Solid dispersion is one of several pharmaceutical technologies that enhance the bioavailability of poorly water-soluble drugs. The objective of this study was to prepare and characterize nifedipin-poloxamer 188 solid dispersion by fusion method. Combination of nifedipin and poloxamer 188 for F1, F2 and F3 were 1:9, 2:8 and 3:7 respectively. The physical mixture and solid dispersions were characterized for particles size distribution, drug-carrier interaction, drug content and dissolution rate. The physicochemical characterization showed a specific characterized of solid dispersion. As indicated from X Ray Diffractograms, DTA thermograms and SEM photographs, nifedipin was in the amorphous form and entrapped in polymer matrix. FTIR results proved no chemical interaction between nifedipin and poloxamer 188. SEM images showed a new morphology of solid dispersions compare with pure drug and physical mixture. The dissolution rate was increased with increasing polymer concentrations. F1 showed the highest dissolution rate among all formulas. Statistic analysis showed a significant differences (P<0.05) of dissolution efficiency among all formulas.